2013
DOI: 10.1371/journal.pone.0070244
|View full text |Cite
|
Sign up to set email alerts
|

The Heterogeneity of Early Parkinson’s Disease: A Cluster Analysis on Newly Diagnosed Untreated Patients

Abstract: BackgroundThe variability in the clinical phenotype of Parkinson’s disease seems to suggest the existence of several subtypes of the disease. To test this hypothesis we performed a cluster analysis using data assessing both motor and non-motor symptoms in a large cohort of newly diagnosed untreated PD patients.MethodsWe collected data on demographic, motor, and the whole complex of non-motor symptoms from 100 consecutive newly diagnosed untreated outpatients. Statistical cluster analysis allowed the identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
143
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(162 citation statements)
references
References 43 publications
14
143
0
3
Order By: Relevance
“…Additionally, cluster analysis from several large early PD and untreated cohorts have all suggested specific NMS dominant or only NMS driven clustering [12][13][14]. This review aims to highlight these phenotypic variants that have been described within the rubric of Parkinson's disease.…”
Section: Why Non Motor Subtypes?mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, cluster analysis from several large early PD and untreated cohorts have all suggested specific NMS dominant or only NMS driven clustering [12][13][14]. This review aims to highlight these phenotypic variants that have been described within the rubric of Parkinson's disease.…”
Section: Why Non Motor Subtypes?mentioning
confidence: 99%
“…Erro et al have conducted a cluster analysis coupled with validated cognitive, motor and non-motor assessments in a untreated PD cohort and found 4 discrete clusters within the cohort termed benign pure motor, benign mixed motor-non-motor, non-motor dominant and motor dominant [12]. The non-motor dominant cluster reported higher urinary dysfuction and a rapid progression rate compared to the benign mixed motor, non-motor cluster.…”
Section: Evidence From Studies In Untreated Pdmentioning
confidence: 99%
“…In the field of personalised medicine, metabotyping may play a role by stratifying patients for the development of tailored healthcare solutions (45) . Examples of this concept are also available from the medical literature where cluster analysis has been used to identify different phenotypes for a range of diseases including chronic obstructive pulmonary disease (46) and Parkinsons disease (47) . This concept has been particularly useful for multisymtomatic and multifactorial diseases where presentation and severity of the disease can differ from one individual to the next.…”
Section: Moving From Individuals To Groups: a Novel Use Of Phenotypinmentioning
confidence: 99%
“…This hypothesis was investigated in a large cohort of newly diagnosed, untreated PD patients. 15 Data were collected on demographics, motor symptoms and NMS from 100 subjects and a cluster analysis performed that allowed the identification of different subgroups of PD patients. Four distinct groups were identified that could be classified as (1) benign pure motor, (2) benign mixed motor-non-motor, (3) non-motor dominant and (4) motor dominant.…”
Section: European Neurological Reviewmentioning
confidence: 99%